MSMEs’ Perspective on Tax Compliance in Malang City: Trust and Power Dynamics Compliance Toward Smart Governance - Subandi, Hendi; Rahmanti, Virginia Nur; Reyhanmulky, Muhammad (Universitas Muhammadiyah Yogyakarta, 2025)
This study explores the dynamics of voluntary and enforced tax compliance strategies among individual and corporate taxpayers in the MSME sector in Malang City through the lens of the Extended Slippery Slope Framework (eSSF) and Smart Governance. A qualitative approach was applied using a phenomenological method within an interpretive paradigm. Data were collected through in-depth interviews with MSME taxpayers and triangulated with perspectives from tax officers at the local tax office (KPP Pratama). The findings reveal that enforced compliance is effective only when supported by strong digital systems and consistent monitoring, while voluntary compliance depends heavily on the professionalism, integrity, and transparency of tax authorities in providing services. Digital innovations, particularly the implementation of the CoreTax system, are perceived as both strengthening government authority and building taxpayer trust, thereby positioning Smart Governance as a key enabler for balanced compliance strategies. This research contributes a novel perspective by qualitatively integrating MSME experiences into the eSSF framework, highlighting how trust and power interact within a digital governance context. The insights are useful for policymakers and the Directorate General of Taxes in designing reforms that strengthen MSME tax compliance and enhance the implementation of Smart Governance in Indonesia.